Educational philosophy in developed countries Japanese as a model (Journal of the College of Basic Education, 2022)
The aim of the current research is to get acquainted with the educational philosophy of education in Japan, and after presenting the research problem, its importance, goal and limitations, it touched on a number of theoretical aspects such as: features of education in Japan, the teacher in the Japanese education system, the principles of learning in Japan, the system of educational management and general organization Academic in Japan, curriculum, construction and development in Japan. Then, in the third chapter, he presented the features of the Japanese educational philosophy, such as: job training, the Japanese experience in educational reform, and education in Japan as a model for kindergarten. In the fourth chapter, he presented aspects that can be used from the Japanese experience in preparing the Iraqi teacher: Benefiting from the Japanese experience in the integration between centralization and decentralization in the management of the educational system, which gives flexibility in management, practice, programs, applications and activities, and the balance between originality and contemporary. Japan benefited from data The Western era adheres to its historical and cultural roots, and develops a sense of responsibility among students that reaches an attempt to raise the dignity of some works that are seen as menial.